2019
DOI: 10.1177/0363546519861965
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Spine Dimensions and Suitability as a Glenoid Bone Graft Donor Site

Abstract: Background: Current structural bone graft options used for glenoid augmentation in glenohumeral instability have known drawbacks. The scapular spine may be a possible alternative graft choice, but its dimensions and anatomy are not fully reported. Hypothesis: The scapular spine’s harvestable graft dimensions will be similar to harvestable dimensions of the coracoid and iliac crest. Study Design: Descriptive laboratory study. Methods: The scapular spine, coracoid, and iliac crest dimensions were recorded and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 53 publications
3
49
1
Order By: Relevance
“…In general, the correlation analyses of our study have shown that the scapular dimensions (scapular length and width; glenoid length and width) might be of value in the diagnosis, assessment, and prevention of SN entrapment syndrome associated with scapulae of type III, IV and VI SSN emphasizing the clinical signi cance of scapular dimensions in helping clinicians, radiologists, and orthopedic surgeons perform better with minimal complications in agreement with previous ndings [1][2][3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, the correlation analyses of our study have shown that the scapular dimensions (scapular length and width; glenoid length and width) might be of value in the diagnosis, assessment, and prevention of SN entrapment syndrome associated with scapulae of type III, IV and VI SSN emphasizing the clinical signi cance of scapular dimensions in helping clinicians, radiologists, and orthopedic surgeons perform better with minimal complications in agreement with previous ndings [1][2][3].…”
Section: Discussionsupporting
confidence: 90%
“…The knowledge of the anatomy and variations of SSN is important for clinicians and surgeons that carry out diagnoses, assessment, management, surgical interventions at the shoulder region. This knowledge is vital in the diagnosis, management, assessment, and prevention of suprascapular nerve entrapment disorder around the shoulder joint [1][2][3]. The suprascapular notch (SSN) forms a depression on the lateral aspect of the superior border of the scapula, medial to the coracoid process [4], is bridged by the superior transverse scapular ligament (STSL), which may sometimes be completely ossi ed with a resultant conversion of the notch into a foramen [4].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the correlation analyses of our study have shown that the scapular dimensions (scapular length and width; glenoid length and width) might be of value in the diagnosis, assessment, and prevention of SN entrapment syndrome associated with scapulae of type III, IV and VI SSN emphasizing the clinical signi cance of scapula, glenoid and other related scapular dimensions in helping clinicians, radiologists, and orthopaedic surgeons. perform better with minimal complications [1][2][3]. However, the equation that can be used to predict the relationship of different scapular dimensions and the SSN types could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…of suprascapular notch variations are important in the management and prevention of the SSN entrapment syndrome, and bony and brachial plexus injuries, furthermore, this knowledge is important for clinicians and surgeons that carry out diagnoses, assessment, management and surgical interventions at the shoulder region and in the prevention of this disorder. [1][2][3]. The suprascapular notch (SSN) forms a depression on the lateral aspect of the superior border of the scapula and located medial to the coracoid process [4], is bridged by the superior transverse scapular ligament (STSL), which may sometime be ossi ed with a resultant conversion of the notch into a foramen [4].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the anatomy and variations of SSN is important for clinicians and surgeons that carry out diagnoses, assessment, management, surgical interventions at the shoulder region. This knowledge is vital in the diagnosis, management, assessment, and prevention of suprascapular nerve entrapment disorder around the shoulder joint [ 1 3 ]. The suprascapular notch (SSN) forms a depression on the lateral aspect of the superior border of the scapula, medial to the coracoid process [ 4 ], is bridged by the superior transverse scapular ligament (STSL), which may sometimes be completely ossified with a resultant conversion of the notch into a foramen [ 4 ].…”
Section: Introductionmentioning
confidence: 99%